Maladaptation of trout spermatozoa to fresh water is related to oxidative stress and proteome changes. Issue 6 (June 2019) - Nynca, J; Słowińska, M; Judycka, S; Ciereszko, A
Abstract : Rainbow trout sperm are 'maladapted' to freshwater spawning, resulting in shorter duration of sperm motility in fresh water compared to buffered saline solution. We hypothesized that different sperm motility-activating media have various effects on sperm motility characteristics and oxidative stress, as well as on the protein profiles of rainbow trout sperm. We designed an experimental model for activation of rainbow trout sperm motility in different osmotic conditions: (i) isosmotic and (ii) hypoosmotic. Spermatozoa activation with hypoosmotic solution was associated with lower values for sperm motility parameters (52%) and an induced increase in ROS level (19.4%) in comparison to isosmotic activation with isosmotic solution (67 and 9.5% for sperm motility and ROS, respectively). Hypoosmotic activation resulted in a higher number of differentially abundant sperm proteins (out of which 50 were identified) compared to isosmotic conditions, where only two spots of protein disulfide-isomerase 6 were changed in abundance. The proteins are mainly involved in the TCA cycle, tight and gap junction signaling, Sertoli cell–Sertoli cell junction signaling and asparagine degradation. Our results, for the first time, indicate that during hypoosmotic activation of sperm motility, osmotic stress triggers oxidative stress and disturbances mostly to structural proteins and metabolic enzymes. Our results strongly suggest that comparative physiological and biochemical analysis of rainbow trout sperm characteristics in isosmotic and hypoosmotic conditions could be a useful model for studying the mechanism of sperm activation in salmonid fish.